Leadership Debacle and Socio-Political Flux in Post Colonial Africa: A Discourse-Stylistic Analysis of Wole Soyinkas A Play of Giants and King Baabu - Samuel Alaba AKINWOTU (Journal of Language and Literature, 2020)
After many years of freedom from colonial domination, African nations are still far from socio-political and economic stability. Post colonial African nations are still battling with socio-political and economic difficulty arising from leadership ineptitude and military dictatorship. Even though democracy has gradually replaced military dictatorship in most of these nations, the success of the democratic experiments have suffered huge setback and these have negatively impacted on the lives of the average citizens. Scholarly interests in the political and economic crises in Africa have been from a wide range of fields and theoretical perspectives including language and literature. Existing works, however, have not adequately explored its representations in the rich literary resources of the continent in spite of its role in record keeping and as the conscience of the society. This is the gap which this study fills. The present study, which adopts discourse-stylistics as theoretical ground, examines leadership crisis vis--vis socio-political flux in selected plays of Wole Soyinka. The paper identifies and describes the features of style in relation to their discourse value and how these have helped in achieving the overall satirical import of the plays. Two of Soyinkas socio-political plays namely; A play of Giants and King Baabu were purposively selected for the study. Through artistic creativity and deployment of language as an ideological satirical tool, Soyinka presents the pitiable picture of the African socio-political system and the ridiculous image of the leadership in Africa. As revealed in their poor command of the English language, Soyinka mocks post colonial African leaders as uneducated, immoral, intellectually bankrupt and pathologically deficient despots. He paints a pitiable picture of the socio-political realities and leadership ineptitude in African nations through the use metaphor and symbolism.